Pengaruh Corporate Social Responsibility dan Corporate Image Terhadap Brand Loyalty: Studi Martha Tilaar Group di Toko Pondok Indah Mall 2 [The Influence of Corporate Social Responsibility and Corporate Image on Brand Loyalty: A Study on Martha Tilaar Group Shop at Pondok Indah Mall] - Hutabarat, Zoel; Fitrianti, Asih (Universitas Pelita Harapan, 2022)
This study aims to identify the effect of corporate social responsibility and corporate image on brand loyalty: a study case on Martha Tilaar Group at Pondok Indah Mall 2. This study uses a quantitative method in which the collection process uses an online questionnaire and uses non-probability sampling techniques with purposive sampling where respondents are respondents who have visited the Martha Tilaar Group store located at Pondok Indah Mall 2. The sample in this study involved 156 respondents which had been obtained from the questionnaires distributed and for data analysis using a partial approach least square (PLS)-structural equation modelling (SEM) with SmartPLS application. The results of this study indicate that there are six variables in which the variables of economic responsibility, ethical responsibility and philanthropic responsibility have a positive effect on corporate image and brand loyalty. Meanwhile, the legal responsibility variable has no positive effect on corporate image and brand loyalty.BAHASA INDONESIA ABSTRACTPenelitian ini bertujuan untuk mengidentifikasi pengaruh antara corporate social responsibility dan corporate image terhadap brand loyalty: studi kasus Martha Tilaar Group di Toko Pondok Indah Mall 2. Penelitian ini menggunakan metode kuantitatif yang di mana proses pengumpulan menggunakan penyebaran kuesioner dengan sistem online dan menggunakan teknik sampling non-probabilitas, dengan purposive sampling yang di mana responden merupakan responden yang pernah melakukan kunjungan ke toko Martha Tilaar Group yang bertempat di Pondok Indah Mall 2. Sampel pada penelitian ini melibatkan 156 responden dan data yang terkumpul diuji dengan menggunakan pendekatan partial least square (PLS)-structural equation modelling (SEM) dengan aplikasi SmartPLS. Hasil penelitian ini menunjukan terdapat enam variabel yang di mana variabel economic responsibility, ethical responsibility dan philanthropic responsibility berpengaruh positif terhadap corporate image dan brand loyalty. Sedangkan untuk variabel legal responsibility tidak berpengaruh positif terhadap corporate image dan brand loyalty.